SELF-EFFICACY SEBAGAI MEDIA PENINGKATAN PROFESIONALISME GURU DI MADRASAH - Baharun, Hasan; Bali, Muhammad Mushfi El Iq; Muali, Chusnul; Munawaroh, Laili (Risâlah, Jurnal Pendidikan dan Studi Islam, 2020)
This study aims to analyze self-efficacy in building the professionalism of Islamic Education teachers at MTs Darul Ulum, Bungatan, Situbondo, East Java. This study uses a qualitative approach with phenomenology. Data collection techniques are carried out through interviews, observation, and documentation. While the data analysis was carried out in a circular manner by following the Spradley model, namely; domain analysis, taxonomy analysis, componential analysis, and discovering cultural themes. The results showed that increasing the professionalism of Islamic Religious Education teachers through self-efficacy at MTs Darul Ulum Bungatan, Situbondo was carried out through; delegation of authority given by the leadership to teachers, strengthening of self-commitment as the basis for strengthening dedication, quality-oriented teacher behavior as an organizational culture and building a positive thinking attitude to strengthen performance and a spirit of dedication.